Effectiveness of Specimen Collection Technology in the Reduction of Collection Turnaround Time and Mislabeled Specimens in Emergency, Medical-Surgical, Critical Care, and Maternal Child Health Departments. Issue 3 (March 2018) - Saathoff, April M.; MacDonald, Ryan; Krenzischek, Erundina
Abstract : The objective of this study was to evaluate the impact of specimen collection technology implementation featuring computerized provider order entry, positive patient identification, bedside specimen label printing, and barcode scanning on the reduction of mislabeled specimens and collection turnaround times in the emergency, medical-surgical, critical care, and maternal child health departments at a community teaching hospital. A quantitative analysis of a nonrandomized, pre-post intervention study design evaluated the statistical significance of reduction of mislabeled specimen percentages and collection turnaround times affected by the implementation of specimen collection technology. Mislabeled specimen percentages in all areas decreased from an average of 0.020% preimplementation to an average of 0.003% postimplementation, with a P < .001. Collection turnaround times longer than 60 minutes decreased after the implementation of specimen collection technology by an average of 27%, with a P < .001. Specimen collection and identification errors are a significant problem in healthcare, contributing to incorrect diagnoses, delayed care, lack of essential treatments, and patient injury or death. Collection errors can also contribute to an increased length of stay, increased healthcare costs, and decreased patient satisfaction. Specimen collection technology has structures in place to prevent collection errors and improve the overall efficiency of the specimen collection process. Abstract : Supplemental digital content is available in the text.